2022
DOI: 10.3389/fpls.2022.941764
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic constraints determine the distribution of heteromorphic leaves along plant vertical height

Abstract: As an interesting and important trait of some drought-tolerant species, heteromorphic leaves are distributed differentially along plant vertical heights. However, the underpinning mechanism for the formation of heteromorphic leaves remains unclear. We hypothesize that heteromorphic leaves are caused by the hydraulic constraints possibly due to the compensation of the changes in functional traits in response to water transport capacity or the reduction of ineffective water loss. In this study, differences in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…This is because plants in these areas are prone to hydraulic failure and drought-induced death due to the fact that they are suffered drought stress ( Körner, 2019 ; Garcia et al., 2021 ). Yang et al. (2022a) has confirmed this speculation that, with the plant development, the progressive increases of gravitational potential between soil and plant canopy and the frictional resistance of water flow in xylem increases xylem tension, which in turn triggers hydraulics dysfunction through embolization.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…This is because plants in these areas are prone to hydraulic failure and drought-induced death due to the fact that they are suffered drought stress ( Körner, 2019 ; Garcia et al., 2021 ). Yang et al. (2022a) has confirmed this speculation that, with the plant development, the progressive increases of gravitational potential between soil and plant canopy and the frictional resistance of water flow in xylem increases xylem tension, which in turn triggers hydraulics dysfunction through embolization.…”
Section: Introductionmentioning
confidence: 53%
“…Midday water potential and the contents of malondialdehyde (MDA), proline, and soluble sugar of leaves were used as the proxies to reflect the drought stress ( Cao et al., 2020 ; Yang et al., 2022a ). Since the young leaves collected in mid-April were too small to meet the experimental measurement requirements, we collected leaves from each selected individual in the peak season of plant growth (early July), and then measured the proxies of drought stress in the laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The P. euphratica tree, a dominant species of the desert, is one tree species in the terrestrial ecosystem that develops strong leaves in the face of environmental changes, which subjects it to long-term drought and salt stress tolerance. Many researchers have found that P. euphratica has a significant strategy to alleviate the increase in hydraulic constraints along vertical heights [178]. Importantly, poplar saplings exhibit a high degree of phenotypic plasticity in response to water-deficit growing conditions, with reductions in hydraulic stem sensitivity and leaf area being particularly important in postponing the onset of hydraulic failure during an induced drought event.…”
Section: Effect Of Water Stress On Hydraulic Traits In P Euphraticamentioning
confidence: 99%